2005
DOI: 10.1097/01.brs.0000173901.64181.db
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Low Back Pain in Patients Referred for Physiotherapy

Abstract: A substantial proportion of patients still experienced some pain and disability at 12 months follow-up. The most stable predictor of prognosis in low back pain was the duration of the current episode. The choice of statistical method influenced the final model; however, changes in the explained variance were small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 24 publications
6
44
0
Order By: Relevance
“…Similar to a another study from our Institute in patients with back pain (33), and similar to our previous study in patients with knee complaints (34), we found no prognostic indicator to be independently associated with a better prognosis for all outcome measures after both 3 and 12 months. Possibly the mechanisms underlying the course of pain and the course of physical functioning are influenced by different variables.…”
Section: Discussionsupporting
confidence: 79%
“…Similar to a another study from our Institute in patients with back pain (33), and similar to our previous study in patients with knee complaints (34), we found no prognostic indicator to be independently associated with a better prognosis for all outcome measures after both 3 and 12 months. Possibly the mechanisms underlying the course of pain and the course of physical functioning are influenced by different variables.…”
Section: Discussionsupporting
confidence: 79%
“…Participants who are referred earlier have a more likely RTW (Ehrmann-Feldman, 1996). The duration of the current episode is also a stable predictor of prognosis in LBP (Bekkering, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Several participants still experienced some pain at 12 months follow-up (Bekkering, 2005). RTW and no medication were found in another study (Iles, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are somewhat lower than previous studies although most previous studies have failed to identify strong predictors of outcome in chronic LBP. Bekkering et al [22] followed a mixed group (acute/chronic LBP) of 500 patients with non-specific LBP for 12 months. This study evaluated prognostic factors associated with pain and disability at 12 months follow-up.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%